2014
DOI: 10.1152/jn.00154.2014
|View full text |Cite
|
Sign up to set email alerts
|

NaV1.5 sodium channel window currents contribute to spontaneous firing in olfactory sensory neurons

Abstract: Frenz CT, Hansen A, Dupuis ND, Shultz N, Levinson SR, Finger TE, Dionne VE. Na V 1.5 sodium channel window currents contribute to spontaneous firing in olfactory sensory neurons. J Neurophysiol 112: 1091-1104. First published May 28, 2014 doi:10.1152/jn.00154.2014.-Olfactory sensory neurons (OSNs) fire spontaneously as well as in response to odor; both forms of firing are physiologically important. We studied voltage-gated Na ϩ channels in OSNs to assess their role in spontaneous activity. Whole cell patchcla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 52 publications
4
42
0
Order By: Relevance
“…These cells can be identified by their specific morphology including a club-shaped soma that is positioned in the most apical MOE layer, extending a thick process towards the basal membrane (Elsaesser and Paysan, 2005). Consistent with a previous report (Frenz et al, 2014), we also noticed a subset of MOE microvillar cells that were labeled for Na v 1.7 (Figures 2B,D). We observed Na v 1.6 immunoreactivity in the apical cytosol of sustentacular cells, a non-neuronal cell type of the MOE with glia-like supportive function (Farbman, 1992).…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…These cells can be identified by their specific morphology including a club-shaped soma that is positioned in the most apical MOE layer, extending a thick process towards the basal membrane (Elsaesser and Paysan, 2005). Consistent with a previous report (Frenz et al, 2014), we also noticed a subset of MOE microvillar cells that were labeled for Na v 1.7 (Figures 2B,D). We observed Na v 1.6 immunoreactivity in the apical cytosol of sustentacular cells, a non-neuronal cell type of the MOE with glia-like supportive function (Farbman, 1992).…”
Section: Resultssupporting
confidence: 93%
“…Using real-time quantitative PCR, we identified six different Na v channel mRNAs in both MOE and VNO, demonstrating that these tissues share the same channels. Our results in the MOE are supported by previous reports that have identified these isoforms by RT-PCR (Weiss et al, 2011; Frenz et al, 2014) and deep RNA sequencing (Ibarra-Soria et al, 2014). In the VNO, Fieni et al (2003) identified mRNAs encoding Na v 1.1, Na v 1.2, and Na v 1.3.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations